Maternal nutrition practices in Uttar Pradesh, India: Role of key influential demand and supply factors (P11-002-19) - Nguyen, Phuong Hong; Kachwaha, Shivani; Avula, Rasmi; Young, Melissa; Menon, Purnima (Oxford University Press, 2019)
Despite strong policy and program commitment, essential maternal nutrition services are not reaching enough women in many countries. This paper examines multi-factorial determinants (personal, family, community, and health services) associated with maternal nutrition practices in Uttar Pradesh, India.